Diagnostics of Flexible Workpiece Using Acoustic Emission, Acceleration and Eddy Current Sensors in Milling Operation - Filippov A. V. Andrey Vladimirovich; Tarasov S. Yu. Sergei Yulievich; Filippova E. O. Ekaterina Olegovna; Chazov P. A. Pavel Andreevich; Shamarin N. N. Nikolay Nikolaevich; Podgornykh O. A. Oleg Anatolievich (2016, 2016)
Title screen